Role Of Corticosteroid in Treatment of Bronchiolitis Presented to Qazi Hussain Ahmad Medical Complex: Role Of Corticosteroid in Treatment of Bronchiolitis - Razzaq, Abdul; Khan, Irfan; Shah, Maarij Ullah; Nawaz, Samia; Zaman, Gul Makay; Shaukat, Asma (Pakistan Journal of Health Sciences, 2025)
Acute bronchiolitis is a major cause of hospitalization in infants and young children, most commonly caused by respiratory syncytial virus (RSV). Despite high spontaneous recovery rates, corticosteroids are frequently used, though their efficacy remains uncertain. Objective: To assess the short-term clinical efficacy of oral corticosteroids compared to placebo in infants with acute bronchiolitis. Methods: This quasi-experimental study was conducted at the Department of Pediatrics, Qazi Hussain Ahmad Medical Complex, Nowshera. A total of 234 children aged 3 months to 2 years with clinically diagnosed bronchiolitis were enrolled. Participants were allocated to receive either oral prednisolone (1 mg/kg/dose) or placebo twice daily for three days, alongside standard supportive care, including inhaled salbutamol. A blinded examiner assessed treatment response on day 3 using a validated respiratory distress score. Clinical improvement was defined as a reduction of more than two points in the score. Results: Clinical improvement was observed in 97.4% of the corticosteroid group and 94.9% of the placebo group. The difference was not statistically significant (p=0.308). Subgroup analyses based on gender, maternal education, socioeconomic status, and maternal occupation showed no significant impact on treatment outcomes. Conclusions: Oral corticosteroids did not significantly improve clinical outcomes compared to placebo in infants with mild to moderate bronchiolitis. Given the high rate of natural recovery and the potential for adverse effects, routine corticosteroid use is not recommended. Further research is needed to identify specific subgroups that may benefit from targeted steroid therapy